Mitochondrial 16S rRNA gene as a molecular marker in the phylogenetic relationships of some Rabbitfishes species (Siganidae: Perciformes) - Najiah M. Alyamani (Open Veterinary Journal)
Background: Siganidae is marine teleost family consists of a single extant genus, Siganus Forsskål, 1775, included 29 recognized species of rabbitfish. Aim: The main goal of this study was the use of mitochondrial 16S rRNA gene as a potential molecular marker in the phylogenetic relationships study of some rabbitfishes species (Siganidae: Perciformes). Methods: The samples were gathered from the Red Sea. The sequences of four rabbitfishes (Siganus argenteus, Siganus luridus, Siganus rivulatus, Siganus stellatus) were deposited into NCBI to gain the accession numbers (PP488874 - PP488877) and then analyzed with their related rabbitfishes depending on available sequence data of the mitochondrial 16S rRNA gene. Results: The results of 16S rRNA sequences illustrated that the average A+T values were greater than C+G. Conclusion: The low genetic distance between Siganus luridus and Siganus rivulatus indicated close linkage between them. [Open Vet J 2024; 14(8.000): 1936-1941]